Aggressive invasive recurrence of a right atrial myxofibrosarcoma. Issue 4 (9th March 2019) - DeAndrade, Diana S.; Kilic, Arman; Christie, Neil A.; Sultan, Ibrahim
Abstract: A 58‐year‐old man presented with left‐sided chest discomfort 9 years ago. At that time a 12‐centimeter extrapleural mass was resected via left thoracotomy. Surgical pathology revealed a low‐grade myxofibrosarcoma. Since that time, he had undergone three separate resections of recurrent left extrapleural masses with sternotomy and thoracotomy. He proceeded to have a five‐year disease‐free interval after which a pericardial mass invading into the right atrial free wall, the atrioventricular groove, and the right coronary artery was identified. Surgical resection was performed with negative margins and the right atrium and atrioventricular groove were reconstructed without any residual tricuspid regurgitation.